When prophecy never fails Myth and reality in a flying-saucer group - Tumminia, Diana G. (Oxford New York Oxford University Press, 2005)
Seekers and setting -- How prophecy never fails -- The process of mythmaking -- The content of Unarian cosmology -- Being a good student -- Students and the reality of past-life therapy -- In the dreamtime -- Death and transition -- Preparation for the landing -- How prophecy endures
Seekers and setting -- How prophecy never fails -- The process of mythmaking -- The content of Unarian cosmology -- Being a good student -- Students and the reality of past-life therapy -- In the dreamtime -- Death and transition -- Preparation for the landing -- How prophecy endures
Includes bibliographical references and index. - Formerly CIP
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Unarius Academy of Science